Neutralizing anti-IL-1 receptor antagonist autoantibodies induce inflammatory and fibrotic mediators in IgG4-related disease - Jarrell, Justin A.; Baker, Matthew C.; Perugino, Cory A.; Liu, Hang; Bloom, Michelle S.; Maehara, Takashi; Wong, Heidi H.; Lanz, Tobias; Adamska, Julia Z.; Kongpachith, Sarah; Sokolove, Jeremy; Stone, John H.; et al. (The journal of allergy and clinical immunology, 2022)
Background - IgG4-related disease (IgG4-RD) is a fibroinflammatory condition involving loss of B-cell tolerance and production of autoantibodies. However, the relevant targets and role of these aberrant humoral immune responses are not defined. - Objective - Our aim was to identify novel autoantibodies and autoantigen targets that promote pathogenic responses in IgG4-RD. - Methods - We sequenced plasmablast antibody repertoires in patients with IgG4-RD. Representative mAbs were expressed and their specificities characterized by using cytokine microarrays. The role of anti-IL-1 receptor antagonist (IL-1RA) autoantibodies was investigated by using in vitro assays. - Results - We identified strong reactivity against human IL-1RA by using a clonally expanded plasmablast-derived mAb from a patient with IgG4-RD. Plasma from patients with IgG4-RD exhibited elevated levels of reactivity against IL-1RA compared with plasma from the controls and neutralized IL-1RA activity, resulting in inflammatory and fibrotic mediator production in vitro. IL-1RA was detected in lesional tissues from patients with IgG4-RD. Patients with anti-IL-1RA autoantibodies of the IgG4 subclass had greater numbers of organs affected than did those without anti-IL-1RA autoantibodies. Peptide analyses identified IL-1RA epitopes targeted by anti-IL-1RA antibodies at sites near the IL-1RA/IL-1R interface. Serum from patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) also had elevated levels of anti-IL-1RA autoantibodies compared with those of the controls. - Conclusion - A subset of patients with IgG4-RD have anti-IL-1RA autoantibodies, which promote proinflammatory and profibrotic meditator production via IL-1RA neutralization. These findings support a novel immunologic mechanism underlying the pathogenesis of IgG4-RD. Anti-IL-1RA autoantibodies are also present in a subset of patients with SLE and RA, suggesting a potential common pathway in multiple autoimmune diseases.
Online verfügbar May 8, 2021
Gesehen am 23.09.2022